1978
DOI: 10.1136/jcp.31.5.493
|View full text |Cite
|
Sign up to set email alerts
|

High mean red cell volume: its incidence and significance in routine haematology.

Abstract: SUMMARY With the advent of electronic particle counters of the Coulter S type the mean cell volume (MCV) has become an integral and useful feature of the red cell profile. Abnormally high values, often of minor degree, are particularly common but their precise clinical significance may be difficult to establish. This study defines the normal range and determines the incidence and distribution of the high MCV in routine hospital practice. Two hundred consecutive adult patients with an MCV of 100 fl or more were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
7
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 20 publications
3
47
7
1
Order By: Relevance
“…As confirmed in the present study, patients with hemochromatosis and HFE C282Y homozygosity diagnosed in medical care rarely have extreme macrocytosis (MCV > 110 fL) and anemia [3,8,10] that are sometimes associated with deficiency of vitamin B 12 or folate [25,29,30]. Anemia is also common among persons with increased MCV due to other causes [3,25,29,30], but evaluation of all possible circumstances associated with macrocytosis or anemia was beyond the scope of the HEIRS Study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As confirmed in the present study, patients with hemochromatosis and HFE C282Y homozygosity diagnosed in medical care rarely have extreme macrocytosis (MCV > 110 fL) and anemia [3,8,10] that are sometimes associated with deficiency of vitamin B 12 or folate [25,29,30]. Anemia is also common among persons with increased MCV due to other causes [3,25,29,30], but evaluation of all possible circumstances associated with macrocytosis or anemia was beyond the scope of the HEIRS Study.…”
Section: Discussionsupporting
confidence: 62%
“…Anemia is also common among persons with increased MCV due to other causes [3,25,29,30], but evaluation of all possible circumstances associated with macrocytosis or anemia was beyond the scope of the HEIRS Study. It has been proposed that supranormal values of MCV could be used to detect hemochromatosis in white persons of western European descent who are receiving routine medical care [31].…”
Section: Discussionmentioning
confidence: 99%
“…McPhedran (1973), Davidson (1978) and Colon-Otero et al (1992) have variously described their fi ndings in patients with macrocytosis [2,3,9]. McPhedran defi ned the cause of macrocytosis in the absence of anemia in 100 consecutive patients and reported that the most common cause of macrocytic anemia was megaloblastic anemia due to vitamin B 12 and folate defi ciency [2].…”
Section: Etiology Of Macrocytic Anemiamentioning
confidence: 99%
“…The discovery, that an anemic patient's erythrocyte is abnormal in size, suggests certain diseases can be suspected or excluded on the basis of this. With the advent of electronic cell counters, the MCV has become an integral and useful feature of the red cell profi le [2,3]. The Coulter counter generates a value for the average volume of red cells, which is important for categorizing the type and cause of anemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation